Impact of technology use on workforce performance and information access in the construction industry - Ramadan, Bassam; Nassereddine, Hala; Taylor, Timothy R. B.; Goodrum, Paul (Frontiers in Built Environment, 2023)
For decades, labor shortage has been a consistent struggle in the construction industry. At the same time, technological innovations have played a central role in the growth and development of an increasingly diverse construction industry. Existing research indicates that technological adoption is crucial for enhancing project productivity. Despite the importance and potential benefits of technology use, no research has yet studied how technology use on-site impact the worker’s performance and the difficulty of the process to access needed information. The objective of this paper is to analyze and understand the impact of on-site technology use on 1) the self-evaluated performance record (including safety, attendance, quality, productivity, and initiative), and 2) the difficulty of the process to access information, of construction workers and frontline supervisors in the construction industry. To achieve the research objective, 2780 construction craft workers and frontline supervisors were surveyed using an online questionnaire. The survey participants were asked to self-evaluate 1) their work personal performance record, and 2) the difficulty of the process to receive or get access to information. The participants were additionally asked to specify whether different listed information technologies, material technologies, and equipment technologies are used on site. The collected data was then analyzed. Key findings indicate that the on-site use of several technologies had statistically significant impact in increased worker performance and information access. This study contributes to the body of knowledge by empirically quantifying the impact of on-site technology use on worker performance and information access in the construction industry.